2013
DOI: 10.1073/pnas.1315520110
|View full text |Cite
|
Sign up to set email alerts
|

The Arabidopsis ZED1 pseudokinase is required for ZAR1-mediated immunity induced by the Pseudomonas syringae type III effector HopZ1a

Abstract: Plant and animal pathogenic bacteria can suppress host immunity by injecting type III secreted effector (T3SE) proteins into host cells. However, T3SEs can also elicit host immunity if the host has evolved a means to recognize the presence or activity of specific T3SEs. The diverse YopJ/HopZ/AvrRxv T3SE superfamily, which is found in both animal and plant pathogens, provides examples of T3SEs playing this dual role. The T3SE HopZ1a is an acetyltransferase carried by the phytopathogen Pseudomonas syringae that … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

14
257
2
5

Year Published

2015
2015
2020
2020

Publication Types

Select...
7
3

Relationship

2
8

Authors

Journals

citations
Cited by 177 publications
(278 citation statements)
references
References 40 publications
14
257
2
5
Order By: Relevance
“…In Arabidopsis, the NLR ZAR1 is required for the recognition of the HopZ1a effector from P. syringae (Lewis et al, 2010). ZAR1 is activated upon acetylation of the pseudokinase ZED1, by HopZ1a (Lewis et al, 2013). Recently, it was reported that ZAR1 is also important for the recognition of the effector AvrAC from Xanthomonas campestris pv campestris (Wang et al, 2015a).…”
Section: Discussionmentioning
confidence: 99%
“…In Arabidopsis, the NLR ZAR1 is required for the recognition of the HopZ1a effector from P. syringae (Lewis et al, 2010). ZAR1 is activated upon acetylation of the pseudokinase ZED1, by HopZ1a (Lewis et al, 2013). Recently, it was reported that ZAR1 is also important for the recognition of the effector AvrAC from Xanthomonas campestris pv campestris (Wang et al, 2015a).…”
Section: Discussionmentioning
confidence: 99%
“…These domains might be involved in the recognition of cofactors and cognate effector proteins (Collier and Moffett, 2009;Lewis et al, 2013) or mediate downstream signaling, eventually leading to the induction of defense responses (Maekawa et al, 2011;Collier et al, 2011;Wang et al, 2015a). The HR can be induced via the activation of downstream signaling by isolated CC domains derived from proteins including MLA10 from barley (Hordeum vulgare; Maekawa et al, 2011), Rp1-D21 from maize (Zea mays; Wang et al, 2015a), Sr33 and Sr50 from wheat (Triticum aestivum; Cesari et al, 2016), and NRG1 or ACTIVATED DISEASE RESISTANCE1 (ADR1) from N. benthamiana and Arabidopsis (Collier et al, 2011).…”
Section: Introductionmentioning
confidence: 99%
“…HopZ1a is part of the YopJ superfamily of T3SEs that are found in animal and plant pathogenic bacteria and is an acetyltransferase (Lewis et al, 2008(Lewis et al, , 2011Lee et al, 2012;Ma and Ma, 2016). Detection of HopZ1a by AtZAR1 requires AtZED1 (HOPZ-ETI-DEFICIENT1), a receptorlike cytoplasmic kinase (RLCK) belonging to the RLCK XII-2 family (Lewis et al, 2013). AtZED1 interacts with AtZAR1 and HopZ1a and is acetylated by HopZ1a, which is hypothesized to trigger the activation of AtZAR1 (Lewis et al, 2013).…”
mentioning
confidence: 99%